Flexible, robust and temperature resistive NIR photodetector based on P-WSe2/P-CuO hybrid on cellulose paper. (2023) - Patel, Rahul P.; Pataniya, Pratik M.; Patel, Meswa; Modi, Krishna H.; Sumesh, C.K.
Abstract: Photodetector based on two dimensional (2D) transitional metal dichalcogenide (TMDC) exhibits fast photo-response with significant stability, but their lack of flexibility, robust nature, and enormous size, limit their versatility. Herein, we fabricated cost effective, near infrared (NIR) paper-based flexible photodetector based on P- type tungsten di-selenide (WSe2 ) and P-type copper oxide (CuO) composite using a non-toxic, solvent free and environment friendly rubbing deposition technique. The electrical and optical properties are tuned due to the formation of a WSe2 /CuO heterostructure, which leads to increased photodetection ability and charge carrier mobility. The bending, twisting, and folding performance reveal the flexible nature of the photodetector, while the stable photoresponse against the different values of pressure and temperature demonstrate the robust and temperature resistive nature of the photodetector. At room temperature and under NIR (780 nm) illumination, the photodetector exhibit photoresponsivity (R) of 2.75 mA/W, a specific detectivity of 0.58 × 10 9 Jones, and external quantum efficiency (EQE) of 0.31 % (at 2.0 V bias). The cost effective, solvent free, and non-toxic fabrication technique of the flexible photodetector could appeal to researchers and the scientific community for the versatile application of the optoelectronic device.